Pieter-Louis Myburgh, The Republic of Gupta: A Story of Sate Capture (Historia, 2021)
In recent years, state capture has entered the political discourse of South Africa. This after a powerful and connected business elite entered the South African political arena and succeeded in capturing key institutions of the state and repurposing themin ways that subvert the constitutional mandate established in 1994. It is imperative to note that systemic corruption/state capture holds serious repercussions for the country’s political and economic fabric. Pieter-Louis Myburgh’s book, The Republic ofGupta: A Story of State Capture, unpacks the degree and extent to which institutionalised corruption has influenced the functionality of the South African state.
Keywords: South Africa; politics; 1994.; State Capture; Gupta; corruption